2016
DOI: 10.1590/s1679-45082016ao3714
|View full text |Cite
|
Sign up to set email alerts
|

Randomized double-blind clinical trial comparing two anesthetic techniques for ultrasound-guided transvaginal follicular puncture

Abstract: Objective:To compare the anesthetic techniques using propofol and fentanyl versus midazolam and remifentanil associated with a paracervical block with lidocaine in performing ultrasound-guided transvaginal oocyte aspiration.Methods:A randomized double-blind clinical trial (#RBR-8kqqxh) performed in 61 women submitted to assisted reproductive treatment. The patients were divided into two groups: anesthetic induction with 1mcg/kg of fentanyl associated with 1.5mg/kg of propofol (FP Group, n=32), in comparison wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Oliveira et al, reported better rates of pregnancy, as well as fertilized oocytes and em-bryos obtained with the use of opioid and propofol against cervical blockad (7). Similar results were obtained in by Saxena in 2016, in which it was shown that the cervical block is ineffective as a single technique for performing puncture (8).…”
Section: Discussionmentioning
confidence: 64%
“…Oliveira et al, reported better rates of pregnancy, as well as fertilized oocytes and em-bryos obtained with the use of opioid and propofol against cervical blockad (7). Similar results were obtained in by Saxena in 2016, in which it was shown that the cervical block is ineffective as a single technique for performing puncture (8).…”
Section: Discussionmentioning
confidence: 64%
“…In (Oliveira Júnior, et al [6] ; Bümen, et al [9] ; Matsota, et al [12] ). Also, remifentanil has the advantage of significantly higher total oocyte number when it was given in continuous intravenous infusion and compare with local anesthesia (Milanini, et al [24] ) or given in GA (remifentanil with either propofol or isoflurane) and compare with sedation (midazolam, diazepam, or propofol) (Hammadeh, et al [25] ).…”
Section: Discussionmentioning
confidence: 99%
“…[4] ). The process is very painful and stressful as the pain is caused by the passage of the needle through the vaginal wall and by the manipulation of the ovary mechanically (Kwan, et al [5] ; Oliveira Júnior, et al [6] ;…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 30 min in the PACU, we evaluated the satisfaction scores of the endoscopists and patients using a visual analog scale (VAS, 0 = dissatisfaction, and 10 = full satisfaction). Patients were considered eligible for discharge with a score ≥ 9, according to the modified Aldrete–Kroulik index [7].…”
Section: Methodsmentioning
confidence: 99%